Preliminary Studies of the Performance of Quinoa (Chenopodium quinoa Willd.) Genotypes under Irrigated and Rainfed Conditions of Central Malawi - Maliro, Moses F. A.; Guwela, Veronica F.; Nyaika, Jacinta; Murphy, Kevin M. (Frontiers in Plant Science, 2017)
The goal of sustainable intensification of agriculture in Malawi has led to the evaluation of innovative, regionally novel or under-utilized crop species. Quinoa (Chenopodium quinoa Willd.) has the potential to provide a drought tolerant, nutritious alternative to maize. We evaluated 11 diverse varieties of quinoa for their yield and agronomic performance at two locations, Bunda and Bembeke, in Malawi. The varieties originated from Ecuador, Chile and Bolivia in South America; the United States and Canada in North America; and, Denmark in Europe, and were chosen based on their variation in morphological and agronomic traits, and their potential for adaptation to the climate of Malawi. Plant height, panicle length, days to maturity, harvest index, and seed yield were recorded for each variety under irrigation at Bunda and Bembeke, and under rainfed conditions at Bunda. Plant height was significantly influenced by both genotype and environment. There were also significant differences between the two locations for panicle length whereas genotype and genotype × environment (G × E) interaction were not significantly different. Differences were found for genotype and G × E interaction for harvest index. Notably, differences for genotype, environment and G × E were found for grain yield. Seed yield was higher at Bunda (237–3019 kg/ha) than Bembeke (62–692 kg/ha) under irrigated conditions. The highest yielding genotype at Bunda was Titicaca (3019 kg/ha) whereas Multi-Hued was the highest (692 kg/ha) at Bembeke. Strong positive correlations between seed yield and (1) plant height (r = 0.74), (2) days to maturity (r = 0.76), and (3) biomass (r = 0.87) were found under irrigated conditions. The rainfed evaluations at Bunda revealed significant differences in seed yield, plant biomass, and seed size among the genotypes. The highest yielding genotype was Black Seeded (2050 kg/ha) followed by Multi-Hued (1603 kg/ha) and Bio-Bio (1446 kg/ha). Ecuadorian (257 kg/ha) was the lowest yielding genotype. In general the seed yields of the genotypes were lower under rainfed conditions than under irrigated conditions at Bunda. The results also highlight the need to continue evaluating a diverse number of cultivars to select for genotypes adapted to specific agro-ecological areas and across seasons in Malawi.